2019
DOI: 10.32598/irj.17.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Climate and Its Affecting Factors Among Rehabilitation Health Care Staff of Hospitals and Rehabilitation Centers in Iran-Tehran

Abstract: Hospitals and clinical centers are concerned about patient safety. Safety climate is a perceived value of safety in an organization that could improve the safety of workers and patients. The present research was conducted to study the safety climate of patients in the hospitals and rehabilitation centers affiliated to the University of Social Welfare and Rehabilitation Sciences. Methods: This descriptive-analytical study was conducted on 300 nurses and nurse's aides (healthcare staff) who were selected by stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…In Aliabadi et al study, among the safety climate components, the element of "management commitment" had a better score than others [16]. Similarly, in Chahak et al study and Khammar et al study, the component of "management commitment" had the highest mean score [18,19]. Kongsvik et al showed that "safety enhancement" was more evident among the safety climate components among the oil and gas industry employees [20].…”
Section: Discussionmentioning
confidence: 99%
“…In Aliabadi et al study, among the safety climate components, the element of "management commitment" had a better score than others [16]. Similarly, in Chahak et al study and Khammar et al study, the component of "management commitment" had the highest mean score [18,19]. Kongsvik et al showed that "safety enhancement" was more evident among the safety climate components among the oil and gas industry employees [20].…”
Section: Discussionmentioning
confidence: 99%
“…The University of Social Welfare and Rehabilitation University o Social Welfare and Rehabilitation Sciences is one of the affiliated universities to the MHME, with the mission of addressing mental health, social aspects, and rehabilitation Statute of the University o Social Welfare and Rehabilitation Sciences. It is imperative to pay attention to the safety, security, and physical and environmental health [20].…”
Section: The Necessity Of Establishment Of Hse Major At the Universitmentioning
confidence: 99%
“…[ 4 ] These factors can cause fatigue in a long time and have adverse effects on their professional activities. [ 5 ] The prevalence of fatigue reported by nurses was 19.9%, and two-thirds of nurses have such experiences in most cases. [ 6 ] Possible consequences of fatigue in the real world are listed as follows: decreasing consciousness ability to process information, levels of immunity, levels of physical and mental health and increasing the reaction time, adverse effects on the safety, individuals functioning, and life quality disorder.…”
Section: Introductionmentioning
confidence: 99%